Mononuclear phagocyte system of human Peyer's patches: an immunohistochemical study using monoclonal antibodies. - Mahida, Y; Patel, S; Jewell, D (1989)
Macrophages in sections of human terminal ileal Peyer's patches were studied using a panel of monoclonal antibodies. Germinal centre macrophages were large and strongly positive for acid phosphatase and stained with antibodies RFD1, RFD9, UCHM1 and other macrophage-specific monoclonal antibodies, but not RFD7. In the macrophages of the dome region there was heterogeneity of size and staining for acid phosphatase. The majority of the RFD1 positive cells in this region appeared to be macrophages. However, no RFD9- or RFD7-positive cells were present. By contrast, RFD7-positive but RFD9-negative macrophages were present in the lamina propria. In the interfollicular areas there were cells with a dendritic morphology which were strongly HLA-DR, HLA-DQ and RFD1-positive, but which did not stain with the other macrophage specific monoclonal antibodies or for acid phosphatase. Some macrophages and lymphocytes in the germinal centre and dome regions expressed interleukin 2 and transferrin receptors. These cells were not present in the adjacent lamina propria.